THE APPLICATION OF VALUE CLARIFICATION TECHNIQUE (VCT) MODEL WITH VIDEO MEDIA IN IMPROVING CIVICS LEARNING ABOUT RESPECT OF COLLECTIVE DECISION AT THE FIFTH GRADE STUDENTS OF SDN I KARANGGADUNG IN THE ACADEMIC YEAR OF 2014/2015 - Purwanti, Umi (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Value Clarification Technique (VCT) Model with Video Media in Improving Civics Learning about Respect of Collective Decision at The Fifth Grade Students Of SDN I Karanggadung in the Academic Year of 2014/2015. The objectives of this research are to improve civics learning about respect of collective decision at the fifth grade students of SDN I Karanggadung in academic year 2014/2015. This research is a collaborative Class Action Research (CAR). Subjects were twenty one studets, consisting of 9 male students and 12 female students. The experiment was conducted in three cycles. The results show that the application VCT model with video media is increased civics learning about respect of collective decision. Keywords: Value Clarification Technique (VCT) model, video media, civics